1988
DOI: 10.2307/2531856
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment-Induced Mortality and Tumor-Induced Mortality on Tests for Carcinogenicity in Small Samples

Abstract: Statistical tests of carcinogenicity are shown to have varying degrees of robustness to the effects of mortality. Mortality induced by two different mechanisms is studied--mortality due to the tumor of interest, and mortality due to treatment independent of the tumor. The two most commonly used tests, the life-table test and the Cochran-Armitage linear trend test, are seen to be highly sensitive to increases in treatment lethality using small-sample simulations. Increases in tumor lethality are seen to affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
302
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(303 citation statements)
references
References 11 publications
0
302
0
1
Order By: Relevance
“…Tests of pairwise comparisons of the neoplastic and non-neoplastic lesions for each exposed group with the controls was conducted using the Poly-k test (24,29,30). A kvalue of 3 was used in these analyses (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tests of pairwise comparisons of the neoplastic and non-neoplastic lesions for each exposed group with the controls was conducted using the Poly-k test (24,29,30). A kvalue of 3 was used in these analyses (30).…”
Section: Resultsmentioning
confidence: 99%
“…A kvalue of 3 was used in these analyses (30). The analysis includes a risk-weight adjustment on animals that died before completion of the study and reports an adjusted rate of lesion incidence.…”
Section: Resultsmentioning
confidence: 99%
“…differential mortality). Bailer and Portier (1988) addressed the survival issue by defining a modified sample size , where δ cij is a weight for animal j in group i. Clearly an animal that developed a tumor was at risk of tumor onset and thus receives a weight of 1.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor data were analyzed for dose response relationship and pairwise comparisons of vehicle control group with each of the treated groups were performed using the Poly-k method described in the paper of Bailer and Portier (1988) and Bieler and Williams (1993). One critical point for Poly-k test is the choice of the appropriate value of k. For long term 104 week standard rat and mouse studies, a value of k=3 is suggested in the literature.…”
Section: Tumor Data Analysismentioning
confidence: 99%